Implikasi Demokrasi Pilkada Serentak 2024 Dan Polarisasi Politik Islam - Al Azis, Muhamad Irfan; Fatimah, Siti (IAIN Metro, 2023)
Indonesia is a country with a democratic system of government. Democracy is understood as a system of government that ensures the welfare of the people. In another sense, democracy is often referred to as government of the people, by the people, and for the people. As a political system, democracy is the most widespread system in many countries because it can regulate and resolve social and political relations within a country. Article 1 Paragraph 3 of the Constitution of the Republic of Indonesia Year 1945. As a state of law that upholds the values of legal norms based on laws and not a state of power, Indonesia has the highest legal norms, namely Pancasila and the 1945 Constitution of the Republic of Indonesia as the center of laws and regulations. Therefore, the existence of guidelines contained in laws and regulations must not conflict with the law. As the pandemic hit the country, a new political model was built with rising political temperatures. This can be seen from the trend caused by the Covid-19 pandemic, where there are still many problems to be resolved and the political map is developing until 2024. Indonesia faces at least two major challenges during this pandemic, namely the pandemic and political polarization. The traces of polarization are also inseparable from previous political struggles, where there are still political traces that continue to influence subsequent political struggles.